Object-based classification approach for greenhouse mapping using Landsat-8 imagery - Chaofan, Wu; Jinsong, Deng; Ke, Wang; Ligang, Ma; Tahmassebi, Amir Reza Shah (International Journal of Agricultural and Biological Engineering, 2016)
Suburban greenhouses with intensive agricultural productivity have increasingly influenced the daily diet and vegetable supply in Chinese cities. With their enormous input of fertilizers and pesticides, greenhouses have considerably changed the local soil quality and environmental risk factors. The ability to obtain timely and accurate information regarding the spatial distribution of greenhouses could make an important contribution to local agricultural management and soil protection. This paper attempts to present a practical framework for extracting suburban greenhouses, integrating remote sensing data from Landsat-8 and object-oriented classification. Inheritance classification was implemented, and various properties, including texture and neighborhood features in addition to spectral information, were investigated through the popular random forest technique for feature selection prior to SVM classification to improve the mapping accuracy. The results demonstrated that object-based classification incorporating non-spectral features yielded a significant improvement compared with the classification results obtained using only the spectral information in traditional per-pixel classification. Both the producer’s and user’s accuracy were higher than 85% for greenhouse identification. Although it remained a challenge to completely distinguish greenhouses from sparse plants, the final greenhouse map indicated that the proposed object-based classification scheme, providing multiple feature selections and multi-scale analysis, yielded worthwhile information when applied to a continuous series of the freely available Landsat-8 imagery data. Keywords: greenhouse, mapping, Landsat-8, object-based classification, feature selection, multi-scale DOI: 10.3965/j.ijabe.20160901.1414 Citation: Wu C F, Deng J S, Wang K, Ma L G, Tahmassebi A R S. Object-based classification approach for greenhouse mapping using Landsat-8 imagery. Int J Agric & Biol Eng, 2016; 9(1): 79－88.